De retorno al espíritu raíz: Propuesta metodológica para la investigación intercultural (2008)
The growing attendance of indigenous students to public and private universities in Bogota has brought about innovative spaces for intercultural discussion that take onnew ways of educating, narrating and researching reality, from the crossing of western thought and ancient knowledge of the country´s native cultures. Within this context, thearticle presents a research methodology for intercultural studiesthat takes into account Colombia´s cultural diversity and characteristic race mixes, as a contribution to the processes of contact, dialogue and coexistence that we have named here "multicultural interactions".